Method And Apparatus For Analyzing A System Design Having A Phased Array Antenna (2012)
Disclosed subject matter is directed to techniques and systems for analyzing a system design having a phase array antenna. In at least one implementation, component models of individual components of the phased array antenna may be provided. The component models may be arranged as a multi-dimensional lookup table (LUT) in some embodiments. A single-channel model of antenna performance may be synthesized for the system design based on the component models. An analysis of the performance of the system design may then be performed using the single-channel model of antenna performance.